2014
DOI: 10.1007/s00125-014-3272-2
|View full text |Cite
|
Sign up to set email alerts
|

Contrasting the clinical care and outcomes of 2,622 children with type 1 diabetes less than 6 years of age in the United States T1D Exchange and German/Austrian DPV registries

Abstract: DPV data indicate that an HbA1c of <7.5% can frequently be achieved in children with type 1 diabetes who are under 6 years old. An improved metabolic control of type 1 diabetes in young patients appears to decrease the risk of DKA without increasing SH. The greater frequency of suboptimal control in young patients in the T1DX compared with the DPV is not fully explained by a less frequent use of insulin pumps and may relate to the higher HbA1c targets that are recommended for this age group in the USA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

14
138
4
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 155 publications
(158 citation statements)
references
References 29 publications
14
138
4
2
Order By: Relevance
“…Additionally, standardized measurements of height and weight using calibrated devices and trained personnel is standard in pediatric endocrine /diabetes clinics taking care of children with T1D. Regarding possible differences in HbA1c measurements, we have previously reported that in both registries HbA1c methods are DCCT standardized and three different sensitivity analyses did not change results in a comparison focused on between-registry HbA1c differences in children <6 years of age (19). However, it is possible that assay variation may mask relationships with HbA1c.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, standardized measurements of height and weight using calibrated devices and trained personnel is standard in pediatric endocrine /diabetes clinics taking care of children with T1D. Regarding possible differences in HbA1c measurements, we have previously reported that in both registries HbA1c methods are DCCT standardized and three different sensitivity analyses did not change results in a comparison focused on between-registry HbA1c differences in children <6 years of age (19). However, it is possible that assay variation may mask relationships with HbA1c.…”
Section: Discussionmentioning
confidence: 99%
“…Missing and inconsistent data are reported back to the centers for correction. Data collection is approved by the ethics committee at Ulm University and by the IRBs at the participating centers (17,18 (19,20). SH was defined by both registries as a hypoglycemic event in which seizure or loss of consciousness occurred.…”
Section: Methodsmentioning
confidence: 99%
“…In world terms, the occurrence of T1DM in children is expressive and its incidence has been increasing around 3% per year (2)(3)(4)(5)(6) . This disease can present long-term complications, and is the cause of high morbidity and mortality with impacts on the quality of life and increasing healthcare costs requiring interdisciplinary interventions, comprehensive care, health education, monitoring/follow-up checkups, surveillance, and rational and efficient use of available technologies (7)(8) .…”
Section: Introductionmentioning
confidence: 99%
“…9,10 Specifically, the fear of hypoglycemia (and its potential detrimental effects on neurocognitive development) leads to worse glycemic control and suboptimal HbA1c levels in this age group. [11][12][13][14] Recent technological advancements with continuous subcutaneous insulin infusion (CSII) pumps and continuous glucose monitors (CGMs) have led to decreased parental anxiety and improved quality of life in the T1D population. [15][16][17][18] Several small studies using AP in young children have shown reduced rates of hypoglycemia, although without significant improvements in glycemic control [19][20][21] as has been seen in older children and adults.…”
mentioning
confidence: 99%
“…Specifically, fear regarding ability of the child to interact with increasingly complex devices and the risk of inadvertent delivery of inappropriate amounts of insulin, leading to either hypoglycemia or hyperglycemia. As the incidence of T1D in young children is on the rise, 13,26 optimal management options, including the use of AP technology, are of great importance.…”
mentioning
confidence: 99%